2022
DOI: 10.1167/iovs.63.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Retinal Layers Linked to Human Contrast Sensitivity Via Deep Learning

Abstract: Purpose Luminance contrast is the fundamental building block of human spatial vision. Therefore contrast sensitivity, the reciprocal of contrast threshold required for target detection, has been a barometer of human visual function. Although retinal ganglion cells (RGCs) are known to be involved in contrast coding, it still remains unknown whether the retinal layers containing RGCs are linked to a person's contrast sensitivity (e.g., Pelli-Robson contrast sensitivity) and, if so, to what extent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 96 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…However, accumulating evidence has shown substantial structural damage (i.e. degeneration of ganglion cell bodies and their axonal and dendritic structures) and functional deficits in the central vision of patients with glaucoma ( Anctil & Anderson, 1984 ; Elze et al, 2015 ; Glen et al, 2012 ; Hood, 2017 ; Hood et al, 2012 ; Hood et al, 2013 ; Hood et al, 2014 ; Kwon et al, 2017 ; Medeiros et al, 2013 ; Ramulu et al, 2013 ; Roux-Sibilon et al, 2018 ; Shamsi, Liu, Owsley, et al, 2022 ; Stievenard et al, 2021 ; D. L. Wang et al, 2015 ; Min Wang et al, 2009 ; Mengyu Wang, Tichelaar, Pasquale, Shen, Boland, Wellik, De Moraes, Myers, Ramulu, Kwon, Saeedi, Wang, Baniasadi, Li, Bex, & Elze, 2020 ). More relevantly, increased parafoveal and peripheral crowding have been observed even in relatively mild and moderate glaucoma ( Ogata et al, 2019 ; Shamsi, Liu, & Kwon, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, accumulating evidence has shown substantial structural damage (i.e. degeneration of ganglion cell bodies and their axonal and dendritic structures) and functional deficits in the central vision of patients with glaucoma ( Anctil & Anderson, 1984 ; Elze et al, 2015 ; Glen et al, 2012 ; Hood, 2017 ; Hood et al, 2012 ; Hood et al, 2013 ; Hood et al, 2014 ; Kwon et al, 2017 ; Medeiros et al, 2013 ; Ramulu et al, 2013 ; Roux-Sibilon et al, 2018 ; Shamsi, Liu, Owsley, et al, 2022 ; Stievenard et al, 2021 ; D. L. Wang et al, 2015 ; Min Wang et al, 2009 ; Mengyu Wang, Tichelaar, Pasquale, Shen, Boland, Wellik, De Moraes, Myers, Ramulu, Kwon, Saeedi, Wang, Baniasadi, Li, Bex, & Elze, 2020 ). More relevantly, increased parafoveal and peripheral crowding have been observed even in relatively mild and moderate glaucoma ( Ogata et al, 2019 ; Shamsi, Liu, & Kwon, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the conventional view that the central vision remains intact until the end stages of glaucoma, recent neuroanatomic and behavioral evidence support the presence of glaucomatous damage in the central vision ( Anctil & Anderson, 1984 ; Chien, Liu, Girkin, & Kwon, 2017 ; Elze, Pasquale, Shen, Chen, Wiggs, & Bex, 2015 ; Glen, Crabb, Smith, Burton, & Garway-Heath, 2012 ; Hood, 2017 ; Hood, Raza, de Moraes, Johnson, Liebmann, & Ritch, 2012 ; Hood, Raza, de Moraes, Liebmann, & Ritch, 2013 ; Hood, Slobodnick, Raza, de Moraes, Teng, & Ritch, 2014 ; Kwon, Liu, Patel, & Girkin, 2017 ; Medeiros, Lisboa, Weinreb, Liebmann, Girkin, & Zangwill, 2013 ; Ramulu, Swenor, Jefferys, Friedman, & Rubin, 2013 ; Roux-Sibilon, Rutgé, Aptel, Attye, Guyader, Boucart, Chiquet, & Peyrin, 2018 ; Shamsi, Liu, Owsley, & Kwon, 2022 ; Stievenard, Rouland, Peyrin, Warniez, & Boucart, 2021 ; Wang, Raza, de Moraes, Chen, Alhadeff, Jarukatsetphorn, Ritch, & Hood, 2015 ; Wang, Hood, Cho, Ghadiali, De Moraes, Zhang, Ritch, & Liebmann, 2009 ). Specifically, a number of retinal imaging studies have shown significant thinning of the retinal nerve fiber layer (RNFL) and the retinal ganglion cell plus inner plexiform layer (RGC+) even in the macular region of glaucomatous eyes ( Hood et al, 2012 ; Hood et al, 2013 ; Hood et al, 2014 ; Shamsi, Liu, Owsley, et al, 2022 ; D. L. Wang et al, 2015 ). It has been reported that such macular damage occurs in up to 80% of patients with mild glaucoma ( Blumberg, Liebmann, Hirji, & Hood, 2019 ; Hood et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%
“…Wai et al showed that eyes with macular disease and good VA have significantly reduced CSF compared with healthy control eyes ( 45 ), and they thought CSF may be able to explain some subjective visual complaints and patients' bad visual experiences while visual acuity may not. Shamsi et al have even put forward the idea that the visual acuity and contrast sensitivity in the foveal region were dissociative ( 46 ). Our study has demonstrated the above-mentioned ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Wang found that the retinal inner layer is associated with reduced contrast sensitivity in retinal vein occlusion ( 47 ). Shamsi et al found that 36% of the variance in the contrast sensitivity could be explained by the retinal structure in patients with glaucoma, age-related macular degeneration, and normal people ( 46 ). In our study, we identified structural changes in the fundus of the eyes of patients with FUS via VD, but no significant correlation was observed between VDs and contrast sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation